Greece, Enosis and Britain’s Complete Evacuation From Greece in March 1947 - Hussain, Norasmahani (European Publisher, 2019)
Greece, a country which borders the Ionian and Mediterranean Sea, was important to Britain. This was due to Greece’s location, which is close to Britain’s sea communications and oil supplies. Therefore, Greece’s safety was of utmost priority to Britain so the latter could secure its predominance in the Mediterranean region. When the Greek Civil War (1946-1949) broke out in March 1946, Britain, and specifically Foreign Secretary Ernest Bevin, determined in helping the Greek Royalist government, fought against Greek communists by providing economic and military support. Should Greece fall under communist influence, Britain would lose its dominance in Greece and the Mediterranean region. However a year later, Britain decided to withdraw its troops even though the Civil War in Greece was not yet over. This article will discuss in detail, from Bevin’s perspective, the decision to withdraw from Greece as he was the one who initially refused to cut military spending in Greece as proposed by the Treasury, and it was he who eventually accepted the proposal. Previous studies have unanimously argued that Britain’s poor economic and military circumstances were Bevin’s greatest worries, which led to Bevin’s decision to discontinue Britain’s aid to Greece. This article, however, will identify Bevin’s other reasons that are absent from the literature. Through the methodology of British primary records, this article found that Greece’s support for the enosis (union) movement, and that Cyprus wanted to be returned to Greece, were also factors that influenced Bevin’s decision to accept the termination of British aid to Greece.